Enterococcus Faecium strain AVG44 - A potential probiotic isolated from human Faecal sample - AVTAR SAIN,; VINAY DUBEY,; ASIT RANJAN GHOSH, (International Journal of Pharma and Bio Sciences, 2018)
Probiotics of human origin is one of the prerequisites for probiotic characteristics along with additional health beneficial properties such as cholesterol assimilation and anti-oxidative properties. A total of 37 strains were isolated from six healthy human volunteers. Among all, one strain (AVG44) was found with probiotic potentials like acid tolerance (103.82% cell viability), bile salt tolerance (108.2% cell viability), cholesterol assimilation (62.2% assimilation), salt aggregation ability (0.15M), lactic acid production (159.79 mg/ml), anti-oxidant and β-galactosidase production. Produced lactic acid was determined using r-HPLC. The strain was found antagonistic to Escherichia coli (ATCC 25922), and Staphylococcus aureus (ATCC 25923).While being sensitive to Chloramphenicol, and Tetracycline, the strain shows resistant to Gentamicin, Nalidixic acid, and Vancomycin. It was identified by 16S rDNA sequencing and was found to be Enterococcus faecium strain AVG44 and showed no heamolysis.AVG44 could thus possibly be a good probiotic strain to elucidate health benefits to human.